Methods to extract and analyze fluid from human pluripotent stem cell-derived choroid plexus organoids - Chew, Leon H.; Mercier, Eloi; Rogalski, Jason C.; Pippard, Sara; Knock, Erin (Frontiers in Molecular Neuroscience, 2024)
The choroid plexus (ChP) is a highly vascularized tissue lining the ventricular space of the brain. The ChP generates cerebrospinal fluid (CSF) and forms a protective barrier in the central nervous system (CNS). Recently, a three-dimensional human pluripotent stem cell (hPSC)-derived ChP organoid model has been developed. This model generates cystic structures that are filled with a fluid resembling CSF and are surrounded by an epithelial layer expressing ependymal choroid plexus-specific markers. Here we describe a method to generate these choroid plexus organoids using a commercial kit and methods to extract the CSF-like fluid for use in downstream analysis.